(untitled) (Research, Society and Development, 2025)
The urinary system is complex, and when bacteria enter these organs, urinary tract infections (UTIs) can develop, affecting individuals of both sexes and all ages. Urinary tract infections (UTIs) are one of the most common diseases and are frequently diagnosed and treated in healthcare settings. Therefore, the objective of this study was to identify the most commonly used medications for urinary tract incontinence in pregnant women. The research was designed as a qualitative, exploratory, descriptive-explanatory study and was conducted through an integrative literature review. Data collection was performed through systematic searches in the PubMed, Virtual Health Library (VHL), and Lilacs databases, using the descriptors "Urinary Incontinence," "Pregnant Women," and "Antibacterials," in Portuguese and English, according to the terminology standardized by the Health Sciences Descriptors (DeCS) and Medical Subject Headings (MeSH). The results showed that E. coli is the most prevalent agent in urinary tract infections during pregnancy, with cephalosporins, amoxicillin, amoxicillin-clavulanic acid, nitrofurantoin, fosfomycin, trimethoprim-sulfamethoxazole, gentamicin, piperacillin-tazobactam, and ciprofloxacin being the most used antibiotics. It was observed that, although some traditional medications present resistance, alternatives such as nitrofurantoin, gentamicin, and ertapenem maintain high efficacy against recurrent pathogens. In conclusion, the data indicates the importance of therapeutic decisions based on up-to-date susceptibility testing, considering maternal-fetal safety and clinical efficacy, to prevent treatment failures and reduce the emergence of antimicrobial resistance.